Francis Bacon and the limits of scientific knowledge - Desroches, Dennis, 1969- (Continuum studies in British philosophy., 2006)
Div & While Francis Bacon continues to be considered the 'father' of modern experimental science, his writings are no longer given close attention by most historians and philosophers of science, let alone by scientists themselves. In this new book Dennis Desroches speaks up loudly for Bacon, showing how we have yet to surpass the fundamental theoretical insights that he offered towards producing scientific knowledge. & br & & br & The book first examines the critics who have led many generations of scholars - in fields as diverse as literary criticism, science studies, feminism, philosophy and history.